Studuis on the Effects of Spacing and Application of Fertilisers on Wood Quality in Eucalyptus tereticornis Sm. - Chauhan, Laxmi; Agrawal, S. P.; Dayal, R. (Indian Forester, 1983)
The results of the study on the effect of spacing and application of fertilise on wood specific gravity, fibre rength and tree groth in 8-year-old experimental plantations of Eucalyptus tereticornis Sm. Laid out in West Bengal and Gujarat are reported here. Spacing as well as application of fertilisers do not show any significant effect on specific gravity. Though the fibre length has heen found to differ significantly among the treatments, the trend is not consistent for any of the treatments in the two localities. While close spacing adversely affect the height and girth of the trees. The effect of application of fertilisers is not significant.